Early markers of periodontal disease and altered oral microbiota are associated with glycemic control in children with type 1 diabetes. Issue 3 (15th December 2020) - Jensen, Emilija D.; Selway, Caitlin A.; Allen, Gabrielle; Bednarz, Jana; Weyrich, Laura S.; Gue, Sam; Peña, Alexia S.; Couper, Jennifer
Abstract: Objectives: To determine the relationship between periodontal disease and glycemic control in children with type 1 diabetes and to characterize the diversity and composition of their oral microbiota. Methods: Cross‐sectional study including children with type 1 diabetes recruited from clinics at the Women's and Children's Hospital (Australia). Participants had a comprehensive dental assessment, periodontal examination, and buccal and gingival samples collected for 16S rRNA sequencing. Results: Seventy‐seven participants (age 13.3 ± 2.6 years, 38 males, BMI z‐score 0.81 ± 0.75) had a diabetes duration of 5.6 ± 3.9 years and median HbA1c of 8.5% (range 5.8–13.3), 69.4 mmol/mol (range 39.9–121.9). Thirty‐eight (49%) had early markers of periodontal disease. HbA1c was positively correlated with plaque index (Rho = 0.34, P = 0.002), gingival index (Rho = 0.30, P = 0.009), bleeding on probing (Rho = 0.44, P = 0.0001) and periodontal pocket depth >3 mm (Rho = 0.21, P = 0.06). A 1% increase in HbA1c was independently associated with an average increase in bleeding on probing of 25% ( P = 0.002) and with an increase in the rate of sites with pocket depth >3 mm of 54% ( P = 0.003). Higher HbA1c was independently related to increased phylogenetic alpha diversity ( P = 0.008) and increased compositional variation (beta diversity P = 0.02) in gingival, but not buccal, microbiota. Brushing frequency, plaque index, and gingival index had a significant effect on microbiota composition, independent of HbA1c. Conclusions: Children with type 1 diabetes showed a continuous relationship between less favorable glycemic control and increased early markers of periodontal disease. Glycemic control was also related to the complexity and richness of the plaque microbiota, with diversity increasing as HbA1c levels increase.